2008
DOI: 10.1038/modpathol.2008.106
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability and aberrant E-cadherin immunostaining of lobular neoplasia and infiltrating lobular carcinoma

Abstract: The distinction between lobular neoplasia and infiltrating lobular carcinoma from ductal neoplasia and infiltrating duct carcinoma with equivocal histologic features may present a challenge as this distinction has important therapeutic implications. Although E-cadherin staining has been of value in helping to make this determination, the variability of the E-cadherin staining pattern and the immunohistochemistry techniques can be problematic in clinical practice. A total of 161 cases of breast lesions previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…E-cadherin was studied in a variety of tumors, mostly in epithelial tumors, such as colorectal carcinoma [9], endometrial carcinoma [10], breast carcinoma [11,12], ovarian carcinoma [13], and gastric carcinoma [14].…”
Section: Introductionmentioning
confidence: 99%
“…E-cadherin was studied in a variety of tumors, mostly in epithelial tumors, such as colorectal carcinoma [9], endometrial carcinoma [10], breast carcinoma [11,12], ovarian carcinoma [13], and gastric carcinoma [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, aberrant E-cadherin expression was identified in occasional lobular CA cases, which was reported in the range of 2% to 16%. [45][46][47][48][49] Harigopal et al 50 reported aberrant E-cadherin staining patterns in 5 invasive mammary CAs. In their study, the aberrant E-cadherin expression was defined as an E-cadherin immunophenotype that did not correspond to the apparent histologic classification of the lesion.…”
Section: Differential Diagnosis Of Lobular Neoplasiamentioning
confidence: 99%
“…Cytokeratin profile in our case, especially diffuse CK7, CK8, CK19 and focal CEA positivity gives support to ductal origin of the tumor. [19][20][21][22] Moreover, the tumor displayed membranous E-cadherin staining which is characteristic of the ductal immunophenotype, [23,24] while HMW CK positivity, histologic appearance and lamellar keratin formation are typical properties of squamous cells.…”
Section: Discussionmentioning
confidence: 99%